On the use of crushed shells of apricot stones as the upper layer in dual media filters - (:unkn) unknown (IWA PUBLISHING, 2003)
The use of crushed shells of apricot stones instead of anthracite coal in dual-media filters is investigated. Turbidity removal efficiencies were measured for several filtration rates in dual media filters composed of shells of apricot stones above silica sand and anthracite coal above silica sand. Backwash (fluidization) experiments were carried out using sieved fractions of crushed shells of apricot stones to establish curves of expansion versus backwash velocity at 25degreesC. Such curves can be used in the design of filters employing this material. It is believed that the use of such a locally available and cheaper alternative filter medium would be of interest in many small water and wastewater treatment systems around the world.
Keywords: filter media; rapid filtration; water treatment